Melamine–ZnI2 as heterogeneous catalysts for efficient chemical fixation of carbon dioxide to cyclic carbonates. Issue 2 (2nd December 2014) - Liu, Mengshuai; Liu, Bo; Shi, Lei; Wang, Fangxiao; Liang, Lin; Sun, Jianmin
Abstract : Melamine–ZnI2 as heterogeneous catalysts showed high activity and versatility for cycloaddition of CO2 to epoxides due to the synergistic effects. Abstract : In this contribution, the combination of melamine with Lewis acid ZnI2 was developed as heterogeneous dual catalysts for the cycloaddition of carbon dioxide with epoxides yielding the corresponding cyclic carbonates. With molar ratio of 1 : 3.3 of ZnI2 to melamine, high yield (96%) and selectivity (99%) of propylene carbonate was obtained at 150 °C and 3.0 MPa for 4.0 h. The binary catalysts were also effectively versatile for CO2 cycloaddition to other epoxides, especially the less active epoxides such as styrene oxide and cyclohexene oxide. Additionally, the catalysts could be separated easily from the products after reaction and then reused efficiently. Furthermore, a possible synergistic catalytic mechanism was proposed, wherein, melamine played the dual roles to activate CO2 and epoxide simultaneously, ZnI2 activated epoxide and subsequently attacked the activated epoxide, the synergetic effects from melamine and ZnI2 promoted the reaction smoothly. The binary catalysts showed the advantages of simple preparation, low cost, abundant availability and high catalytic activity for CO2 chemical fixation into valuable chemicals.